Psychological distress among infectious disease physicians during the response to the COVID-19 outbreak in the Republic of Korea - Park, Se Yoon; Kim, Bongyoung; Jung, Dong Sik; Jung, Sook In; Oh, Won Sup; Kim, Shin-Woo; Peck, Kyong Ran; Chang, Hyun-Ha (BMC public health, 2020)
Background This study aimed to investigate psychological distress among infectious disease (ID) physicians during the coronavirus disease 2019 (COVID-19) outbreak in the Republic of Korea. Methods Using an online-based survey link sent via text message and email, we conducted a survey from April 21 to 25, 2020, targeting all ID physicians currently working in ID ( n = 265). The questionnaire was based on the Maslach Burnout Inventory-Human Services Survey and the Depression, Anxiety, and Stress Scales, and information was collected on factors protecting against psychological distress and difficulties in relation to COVID-19. Results Of 265 ID physicians, 115 (43.3%) responded, showing burnout (97, 90.4%), depression (20, 17.4%), anxiety (23, 20.0%), and stress (5, 4.3%). There were no differences in terms of distress between ID physicians who were directly involved in the care of patients with COVID-19 or not. Greater than 50% of physicians valued their work and felt recognized by others, whereas < 10% indicated that sufficient human and financial support and private time had been provided during the outbreak. The most challenging issues concerned a lack of attending physicians caring for COVID-19 patients or infection control practitioners, a shortage of personal protective equipment or airborne infection isolation rooms, pressure for research, and lack of guidelines for COVID-19 management. Conclusions During the COVID-19 outbreak in the Republic of Korea, most respondents reported psychological distress. Preparing strategies to secure human resources are crucial to prepare effectively for future epidemics and pandemics.